2016
DOI: 10.1213/ane.0000000000001234
|View full text |Cite
|
Sign up to set email alerts
|

Physostigmine and Methylphenidate Induce Distinct Arousal States During Isoflurane General Anesthesia in Rats

Abstract: Background Although emergence from general anesthesia is clinically treated as a passive process driven by the pharmacokinetics of drug clearance, agents that hasten recovery from general anesthesia may be useful for treating delayed emergence, emergence delirium, and post-operative cognitive dysfunction. Activation of central monoaminergic neurotransmission with methylphenidate has been shown to induce reanimation (active emergence) from general anesthesia. Cholinergic neurons in the brainstem and basal foreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
(61 reference statements)
1
27
0
Order By: Relevance
“…However, acute activation of BF cholinergic neurons by optogenetic method cannot directly induce reanimation from continuous isoflurane administration, even at a concentration as low as 0.7%. The findings are consistent with those of a previous study that found that physostigmine, a centrally acting cholinesterase inhibitor, failed to restore consciousness in rats exposed to 0.9% isoflurane (Kenny et al, 2016). Our study further supports that cholinergic activation in not all brain regions can induce reanimation from anesthetized animals (Pal et al, 2018), which also helps explain why physostigmine in the previous study was unable to restore righting during continuous isoflurane administration (Kenny et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…However, acute activation of BF cholinergic neurons by optogenetic method cannot directly induce reanimation from continuous isoflurane administration, even at a concentration as low as 0.7%. The findings are consistent with those of a previous study that found that physostigmine, a centrally acting cholinesterase inhibitor, failed to restore consciousness in rats exposed to 0.9% isoflurane (Kenny et al, 2016). Our study further supports that cholinergic activation in not all brain regions can induce reanimation from anesthetized animals (Pal et al, 2018), which also helps explain why physostigmine in the previous study was unable to restore righting during continuous isoflurane administration (Kenny et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…4042 Although anesthesiologists have pharmacological tools to antagonize specific drugs acting at specific receptors (e.g., benzodiazepines), 43 only recently has research focused on reversing anesthetic effects by promoting arousal systems. 13,12,46,8 This has been typically accomplished by either pharmacological manipulation using catecholamine reuptake inhibitors, 3,12 dopamine agonists, 4 central nervous system stimulants, 13 and nicotine, 1,3,12,4,6 or by electrical stimulation of specific brain regions such as the ventral tegmental area 5 or parabrachial nucleus. 8 In many of these studies, resumption of righting response (as a surrogate for emergence) was restored while the animal was still exposed to general anesthetics and a direct arousal promoting effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…2 Increasing cholinergic tone through acetylcholinesterase inhibitors has been shown to induce electroencephalographic effects related to arousal and has reversed both sevoflurane- and propofol-induced unconsciousness in humans. 10,11 Most recently, there has been a focus of dopaminergic modulation through the administration of methylphenidate, 3,12,13 dopamine agonists, 4 or direct electrical stimulation of the ventral tegmental area; 5 Solt and colleagues have demonstrated that these pharmacological and nonpharmacological interventions induce reanimation in animals exposed to continuous propofol or isoflurane. 8 In terms of accelerating recovery after anesthetic discontinuation, caffeine has been recently shown to reduce the time to emergence from both propofol and isoflurane.…”
Section: Introductionmentioning
confidence: 99%
“…One interpretation is to acknowledge that monoaminergic systems act subcortically to promote arousal (Brown et al 2012;Solt et al 2014) and that additional transmitters such as orexin (Mieda 2017) and histamine (Brown et al 2012) also promote wakefulness. Concurrent inhibition of all arousal systems in all brain regions is not necessary for anestheticinduced loss of wakefulness (Gompf et al 2009), and different wakefulness promoting systems have been shown to produce differing traits of arousal during the state of isoflurane anesthesia in rat (Kenny et al 2016).…”
Section: State Prediction Irfmentioning
confidence: 99%